KAJIAN REPRESENTASI INDONESIA PADA KARAKTER GATOTKACA DALAM GIM MOBILE LEGENDS MENGGUNAKAN METODE TRIANGULASI - Peter Rhian Gunawan; Berti Alia Bahaduri (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
Gatotkaca is one of the famous heroes in Indonesian pop culture originating from the Mahabharata Indian literary work. In Indonesia, Gatotkaca is widely displayed in puppet shows. In modern times, Gatotkaca has been widely adopted into advertisements, comic books, caricatures, and recently into an online game called Mobile Legends Bang Bang. In Indonesia, Mobile Legends Bang Bang has the largest number of players compared to the number of players from other parts of the world. In the development of the game, Mobile Legends makes the hero was taken from Indonesia, Gatotkaca, into their list of heroes that can be chosen by players. The developer of this game hopes that this character can represent players from Indonesia and add to the appeal of this game. The initial assumption of this research is that the generation of players aged 15-30 years possibly does not recognize the Indonesian characteristics in the character visualization developed by Monsoon since this company is a global company that is not from Indonesia. This study aims to explore the extent to which young Indonesian players can recognize the Gatotkaca character in the Mobile Legends game and find out what myths Monsoon wants to build through the Gatotkaca character, which makes Indonesian players interested in playing it. Researchers use questionnaires and focus group discussions in gathering the necessary information. The results from the respondents and FGD then triangulated with Barthes's semiotics to compare data. The mythical representation found is that the character of Gatotkaca is the only male hero representing Indonesia who has the power of a god, very masculine and unfriendly, but has the majesty of a king. Respondents can identify Gatotkaca as characters from Indonesia based on visual costumes, but not all visual aspects of Gatotkaca represent Indonesia. In addition, there are misperceptions by generations of players from 15-30 years of the Indonesian identity. The existence of Gatotkaca characters does not affect their character selection when playing Mobile Legends.